Post‐myocardial Infarction Intraventricular Conduction Defects and B‐type Natriuretic Peptide Levels - Ciuraszkiewicz, Katarzyna (Clin Cardiol, 2009)
BACKGROUND: Levels of B‐type natriuretic peptide (BNP), a significant marker of left ventricular (LV) dysfunction, may provide information on the severity of heart failure in patients with intraventricular conduction defects (IVCD).The aim of this study was to measure serum BNP levels in post‐myocardial infarction (MI) patients with IVCD. METHODS: In 2004–2005 during standard follow‐up at 6 mo after acute MI in 158 subjects, BNP was measured using an immunoenzymatic method. Of them, 126 patients had IVCD: 31, left bundle branch block (LBBB); 36, right bundle branch block (RBBB); 30, left anterior hemiblock (LAH); and 29, left posterior hemiblock (LPH). Thirty two patients with a previous MI, but without IVCD, served as controls, whereas 15 healthy subjects entered the comparative group. RESULTS: In post‐MI patients with IVCD, the mean BNP level was significantly higher than in their counterparts without IVCD (p < 0.001) and in healthy subjects (p < 0.001). The highest BNP level was found in patients with LBBB and RBBB. In patients with LAH and LPH, levels of BNP were insignificantly higher than in patients without IVCD. CONCLUSIONS: Significantly higher BNP levels in patients with previous MI and IVCD suggest more severe heart failure than in their counterparts without IVCD with comparable LV ejection fraction. Copyright © 2008 Wiley Periodicals, Inc.